The auditory system : anatomy, physiology, and clinical correlates - Musiek, Frank E.; Baran, Jane A. (Plural Publishing, Inc., 2020)
This updated, second edition of The Auditory System: Anatomy, Physiology, and Clinical Correlates remains an essential text for audiology students and clinicians. The text is designed to provide comprehensive coverage of the anatomy and physiology of the central and peripheral auditory systems. Readers will benefit from the important link between science and clinical practice, with integrated clinical correlates found in each chapter. Key Features: Presents balanced coverage of both the peripheral and central auditory systems Integrated clinical correlates establish the link between science and practice Substantial use of review articles and secondary sources enhances general understanding Numerous anatomical sketches and photographs supplement learning New to this Edition: A newly designed color interior and many full color images provide increased readability A new chapter providing an overview of normal development of the auditory system, plasticity of the central auditory system, and aging effects on the peripheral and central auditory systems A number of new illustrations New and updated information on synaptic ribbons, neuropharmacology of cochlear function, cryoloop cooling, and the vascular network of the brainstem Updated references, review articles, and readings The Auditory System: Anatomy, Physiology, and Clinical Correlates, Second Edition is an essential text for graduate programs in audiology and a valuable reference for audiologists at any stage of their career.